Interactional Metadiscourse Markers in the U.S. House Republican Primary Debate - Oktavia, Tiara Agil Tri; Ekawati, Rosyida (Talenta Publisher, 2024)
This study aims at explaining the types and functions of interactional metadiscourse markers in the U.S. House Republican primary debate. It is a descriptive qualitative method because the data in this study are the form of words. The source of the data in this study is debate transcripts, while the data are the words, phrases, and sentences in the debate which contain the categories of interactional metadiscourse markers. The results of the study show that there are five types of interactional metadiscourse markers. Those are hedges, boosters, attitude markers, self-mentions, and engagement markers. Self-mentions are the most dominant markers used by the candidates which reach a total of 149 data. Meanwhile, the lowest marker is hedges with a total of 62 data. In addition, the writer also found that each marker has its own function. Hedges aim to show that the speaker's statements are more reasonable opinions than facts. Boosters are used to emphasize or clarify a statement. Attitude markers have a function to show the speaker's attitude towards a proposition. Then self-mentions are used to explicitly show the speaker's presence in the discourse. Meanwhile, engagement markers are used to focus the audience attention or involve them in the discourse.